Identification and Registration Practices in Transnational Perspective
X, 344 p.
Keywords: This collection examines the subject of identification and surveillance from 16th C English parish registers to 21st C DNA databases. The contributors, who range from historians to legal specialists, provide an insight into the historical development behind such issues as biometric identification, immigration control and personal data use.